Case Report: Young Adults With Breast Cancer: A Case Series of Fertility Preservation Management and Literature Review - Ahmad, Mohd Faizal; Sugishita, Yodo; Suzuki-Takahashi, Yuki; Sawada, Shino; Iwahata, Hideyuki; Shiraishi, Eriko; Takae, Seido; Horage-Okutsu, Yuki; Suzuki, Nao (Frontiers in Medicine, 2021)
Breast cancer comprised at least 21.8.% of the overall cancer among young adult (YA) women and became the leading cancer in this group in Japan, with 50% adolescent and YAs being diagnosed and 15–44-year-old women showing excellent 5-year survival. Surgical-chemoradiation therapy often results in excellent survivorship with an increased incidence of treatment-induced subfertility. Therefore, adding fertility preservation (FP) to the primary cancer treatment is necessary. Herein, we reported a series of cases of YA women with breast cancer who opted for FP, where their option was tailored accordingly. To date, the selection of oocytes, embryos and ovarian tissue is widely available as an FP treatment. PGT could reduce the risk of BRCA mutation transmission amongst BRCA carriers before pregnancy planning. Otherwise, gonadotropin-releasing hormone analog has no gonadoprotective effect and thus should not be considered as an FP option.